Estimates of Government Net Capital Stocks for 26 Developing Countries, 1970-2002 - Arestoff, Florence (World Bank, Washington, DC, 2012)
The authors provide various estimates of the government net capital stocks for a panel of 26 developing countries over the period 1970-2001. Two kinds of internationally comparable series of public capital stocks are presented. The first estimates are based on the standard perpetual inventory method and various assumptions regarding initial stocks and depreciation rates. The second set of estimates takes into account the potential inefficiency of public investments in creating capital with a nonparametric approach. Three estimates of net capital stocks are provided, on the basis of three assumptions regarding the efficiency of public investment.